Newly assembled mitochondrial genomes of Hypericum (Hypericaceae) provide insights into phylogenetic relationships and inter-organellar conflict - Yu, Jia-Xin; Bai, Rui-Zhu; Chen, Ya-Ping; Ma, Xiao-Lei; Celep, Ferhat; Xiang, Chun-Lei (Frontiers in Plant Science, 2026)
Hypericum is the largest genus in Hypericaceae and is widely recognized for its medicinal importance. To investigate the evolutionary dynamics of the genus, we assembled and annotated the first mitochondrial genomes of H. ascyron (411,519 bp) and H. perforatum (485,128 bp). Both genomes were recovered as circular structures and contained 30 conserved protein-coding genes (PCGs). Phylogenetic analyses based on 29 mitochondrial PCGs resolved Hypericaceae as sister to Podostemaceae, forming a distinct clade closely related to Calophyllaceae. Notably, we detected topological incongruence between mitochondrial and plastid phylogenies for H. hirsutum, H. pulchrum, and H. perforatum, indicating inter-organellar conflict within the genus. In addition, 316–324 RNA editing sites were predicted, many of which resulted in non-synonymous codon changes. These newly generated mitogenomes represent valuable genomic resources and provide new insights into the genetic diversity and evolutionary complexity of Hypericum.